النفاعل الصفي من وجهة نظر المعلمين في ظل المنشور الوزاري229 المؤرخ في 14/09/2023 المتعلق بمواقيت مرحلة التعليم الابتدائي - غراب خديجة (جامعة الوادي - University of Eloued, 2025)
"اسة بالعربية :ممخص الدر اسة إلى الكشف عمى مدػ تأثرىدفت ىذه الدرؼارالمنشكر الكز229خ فيالمؤر14 سبتمبر2023حمة التعميـ االبتدائي عمى التفاعل الصفي في الطكرالمتعمق بمكاقيت مر االبتدائي حيث تمت صياغةاإلشكاليةالعامة عمى النحك التالي ،(التفاعلالصفي مف كجية المتعمميف في ظل المنشكر229خ فيالمؤر14سبتمبر623حمة التعميـالمتعمق بمكاقيت مر االبتدائي ) كقد شممتاسةعينة الدر100معمـ كمعممةكقدتـإتباع في معالجة البيانات عمى المنيج الكصفي االستكشافي ، ثـاستخدمناكلات كالنسارمف التكرب المئكيةكبعدتطبيق األدكات المستخدمة كاستخبلص النتائج تـالتكصل الى ما يمي : -تقييـ تركيز التبلميذ أثناء الدكاـ الثاني مقارنة بالدكاـ األكؿمتكسطة -ح األسئمة بيف الدكاميف : فرؽ طفيف .فرؽ في إستجابة التبلميذ لطر -تقييـ مدػ مشاركة التبلميذ في األنشطة التعممية خبلؿ الدكاـ الثاني:جيد . -مدؼات التدريس المسائية عمى التفاعل الصفيتؤثر فترضعيف. -ىاؽ بيف التبلميد خبلؿ الدكاـ الثتغير في مستكػ التعب كاإلراني:انادر. -لديؾ صعكه في الحفاظ عمى انضباط التبلميذ في الحصصالمسائية:ضعيف" "Abstract: This study aimed to explore the extent to which Ministerial Circular No. 229, dated September 14, 2023, related to the schedules of the primary education stage, affects classroom interaction in primary school. The general research problem was formulated as follows: (Classroom interaction from the perspective of learners in light of Circular No. 229, dated September 14, 2023, related to the schedules of the primary education stage). The study sample included 100 male and female teachers. The descriptive exploratory method was followed in processing the data, and frequencies and percentages were used. After applying the tools and extracting the results, the following findings were reached: - The concentration level of students during the second shift compared to the first shift was moderate. - There was a slight difference in students’ responsiveness to asking questions between the two shifts. - The level of students’ participation in learning activities during the second shift was good. - The impact of afternoon teaching periods on classroom interaction was weak. - Change in the level of fatigue and exhaustion among students during the second shift was rare. - Difficulty in maintaining student discipline during afternoon sessions was weak.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: المنشور الوزاري; تلاميذ الابتدائي; التفاعل الصفي; Minister Ciculer; Classroom interaction; primary school students